A MODEL OF READING MATERIALS FOR PUBLIC HEALTH STUDENTS, FACULTY OF HEALTH SCIENCES, MUHAMMADIYAH UNIVERSITY OF PONTIANAK - Yuniarti, .; ., Sudarsono; Sada, Clarry (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2016)
Abstract:Teaching reading for specific purposes requires proper teaching and learning materials as the materials play significant roles in teaching process. The present, reading materials for Public Health students of Muhammadiyah University of Pontianak are still very far from students? need. This study aimed at developing a model of reading materials for Public Health students. Using a development study of ADDIE instructional design of Dick and Carrey, twenty five second semester students of Health Sciences Faculty, Muhammadiyah University of Pontianak, participated in this study. The results revealed that the reading materials that were developed in ADDIE model were accepted by both experts and the students. The materials aligned to the learning aims, covered the  student-centered activity, Public Health topic, easy to difficult vocabulary level, student-centered activity and glossary study,  and provided in graded and assorted tasks. It is highly expected that this study will encourage the lecturers of English subject to be more active in developing qualified teaching materials as both lecturers and students will be  helpful and facilitative with the product. Key words:  Reading Materials, Students? Need, Developing Materials, English For Public Health. Abstrak:Pengajaran Reading untuk keperluan khusus memerlukan materi pengajaran yang sesuai dan tepat karena materi memiliki peran yang sangat penting salam proses pengajaran dan pembelajaran.. Penelitian ini bertujuan untuk mengmbangkan materi Reading bagi mahasiswa jurusan fakultas Ilmu Kesehatan, Universitas Muhammadiyah Pontianak. Penelitian ini menggunakan model pengembangan bahan ajar ADDIE oleh Dick & Carey. Sebanyak 25 mahasiswa semester 2  jurusan Kesehatan Lingkungan di pilih secara acak sebagai peserta penelitian. Hasil penelitian yang dilakukan melalui 5 tahap prosedur pengembangan ADDIE  membuktikan bahwa materi yang dikembangkan diterima baik oleh validasi ahli, dosen, dan mahasiswa. Hal ini dapat dilihat dari adanya kesesuaian materi dan tujuan pengajaran, ketepatan pemilihan topik, kesesuaian tingkat kesulitan (mudah ke sulit), adanya glossary study, keragaman latihan  dan acktivitas yang berbasis pada student-centered learning. Hasil penelitian ini diharapkan dapat meningkatkan kreatifitas dosen bahasa Inggris untuk mengembangkan / mendisain bahan ajar yang berkualitas sehingga dapat digunakan secara efektif oleh dosen maupun mahasiswa. Kata kunci: Bahan Ajar reading, Kebutuhan Peserta Didik, Pengembangan Materi, English for Public Health.